2019
DOI: 10.1016/j.yebeh.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric disorders in Thai patients with epilepsy

Abstract: Background: Many studies have shown that the prevalence of psychiatric disorders in patients with epilepsy (PWE) appears higher than that in general population. However, most epidemiological studies regarding psychiatric comorbidities among PWE were conducted in Western countries. This work aimed to determine the prevalence of psychiatric disorders in Thai PWE, including potential variables that could be associated with psychiatric disorders. Methods: A cross-sectional study was conducted at Ramathibodi Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
(65 reference statements)
1
10
1
Order By: Relevance
“…Spread of psychiatric disorders in people suffering from epilepsy and in the general populationIn percentage ratio, out of the patients with mental illness(18), depressive patients were 27.8%, which fell within the range indicated in the world literature. They also have the highest relative share among all patients, as described by other authors.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Spread of psychiatric disorders in people suffering from epilepsy and in the general populationIn percentage ratio, out of the patients with mental illness(18), depressive patients were 27.8%, which fell within the range indicated in the world literature. They also have the highest relative share among all patients, as described by other authors.…”
supporting
confidence: 83%
“…Epidemiological studies have shown that psychiatric disorders are more prevalent among people with epilepsy than in the general population (14-17). (18). A recent study of 770 patients showed that depression and suicidal ideation were common in patients with epilepsy (19).…”
Section: Introductionmentioning
confidence: 99%
“…The result of this study conducted in Mexico (38.8%) (Lopez‐Gomez et al, 2008) and with the other study conducted in Canada (40%) (Pham et al., 2017), Brazil (39.4%) (Stefanello et al., 2011), United Arab Emirate (43.5) (Alsaadi et al., 2015), and Emanuel specialized mental health hospital of Ethiopia (33.5%) (Tegegne et al., 2015). Anxiety disorder symptoms in this study (38.3%) is higher when compared with the other study conducted in Iran (24.5%) (Asadi‐pooya, 2011), Australia (20.2%) (Scott et al., 2017), India (11.0%) (Rehman et al., 2017), Korea (15.3%) (Kwon & Park, 2013) and Thailand (5.3%) (Kuladee et al., 2019). In contrast, the result of these studies (38.3%) is lower when compared with the study conducted in China (57.0%) (Sujithra, 2014), Oman (45.0%) (Al‐asmi et al., 2012) and west Shewa of Oromia (47.8) (Takele & Adamu, 2019).…”
Section: Discussioncontrasting
confidence: 52%
“…A total of 17 studies were included in the final analysis. 7,8,16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] Figure 1 presents a flow diagram detailing the selection process. Out of the 17 studies, 7 provided prevalence estimates for only BS, 8 provided prevalence estimates for only BD, and 2 provided prevalence estimates for both BS and BD.…”
Section: Resultsmentioning
confidence: 99%